(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2016)
The objective of this research was to find out the improvement of content and organization in writing skill by using Sedona Method at the Tenth Grade Students of SMA Batara, Gowa. The researcher used A Classroom Action Research (CAR). The Researcher had conducted two cycles, where each cycle consisted of four meetings. This classroom Action Research (CAR) was at The Eighth Grade of SMA Batara Gowa, Class XB. As the subject in this research was the X Grade with students’ number as about 29 students. The instruments were writing test and observation sheet. The application of Sedona Method can improve the students’ writing, especially in content and organization. This leads to the conclusion that application of Sedona Method was needed in the English Language teaching and learning in improve their competence to organize their idea. Sedona Method that was focused on the learners can engage the students to organize their ideas better than before. The findings of the research were (1) the students’ content achievement was improved 9.98% from diagnostic test to cycle 1 and was improve 10.03% from cycle I to cycle II (2) the students’ organization achievement was improving 8.63% from diagnostic test to cycle I and improved 10.03% from cycle I to Cycle II. From the description above it could conclude the improving of the students’ writing skill in the descriptive paragraph in terms of content and organization by using Sedona Method at the Tenth Grade of SMA Batara Gowa was improved. Keywords: Writing Skill, Sedona Method